2021
DOI: 10.1007/s11356-021-12838-5
|View full text |Cite
|
Sign up to set email alerts
|

Foreign investment, economic growth, and environmental degradation since the 1986 “Economic Renovation” in Vietnam

Abstract: Vietnam has achieved impressive economic growth principally supported by foreign direct investment (FDI) in the last three decades. However, environmental deterioration is observed. No studies have ever been conducted to examine the link between economic growth and environmental degradation, focusing on the important role of the FDI, in Vietnam in both short run and long run. Using the ARDL and the threshold regression techniques for 35 years from 1986, Vietnam's "Doi Moi" (economic renovation), the U-shaped r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The relationship between economic growth and environmental degradation is shown in the environmental Kutznets curve (EKC). The EKC hypothesis presents a bell-curved relationship between economic growth and CO 2 emissions and its validity in the context of Vietnam has recently been studied [18]. In that study, Vo and Ho utilized the auto-regressive distributed lags (ARDL) model to investigate both short-term and long-term relationships between variables and grouped different energy consumption types into two ▶Fig.…”
Section: Economicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between economic growth and environmental degradation is shown in the environmental Kutznets curve (EKC). The EKC hypothesis presents a bell-curved relationship between economic growth and CO 2 emissions and its validity in the context of Vietnam has recently been studied [18]. In that study, Vo and Ho utilized the auto-regressive distributed lags (ARDL) model to investigate both short-term and long-term relationships between variables and grouped different energy consumption types into two ▶Fig.…”
Section: Economicsmentioning
confidence: 99%
“…Aslan et al [19] found that the effect of economic growth on CO 2 emissions in the United States of America was increasing from 1982 to 1996 and decreasing from 1996 to 2013. In Vietnam, CO 2 emissions have increased approximately ten times while economic growth has increased five times from 1986 to 2018 [18]. Energy consumption has tremendously increased, 14 times by fossil sources and more than 50 times by renewable energy sources [18].…”
Section: Economicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another econometric problem faced by researchers is the omitted variables bias (Agras and Chapman, 1999;Harbaugh et al, 2002;Richmond and Kaufmann, 2006;Stern, 2017). To mitigate this problem, several EKC analyses take other variables into account, such as renewable energy consumption (Antonakakis et al, 2017;Danish et al, 2017;Erdogan et al, 2020;Pata and Caglar, 2020;Vo and Ho, 2021), oil prices (Balaguer and Cantavella, 2016;Boufateh, 2019;Malik et al, 2020), and among others. In the present study for Vietnam, we will shed light on the influence of renewable energy consumption and oil prices in driving coal consumption because it has been widely discussed in the field.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…As a result, Vietnam is largely dependent on imported coal for its energy needs (Nguyen et al, 2019;Thong et al, 2021) and especially susceptible to energy prices (Apergis and Gangopadhyay, 2020;Pham and Le, 2020). Meanwhile, the reliance on fossil fuels like coal has spurred concerns over adverse consequences on the environment (Al-Mulali et al, 2015;Finenko and Thomson, 2014;Vo and Ho, 2021). In conjunction with the global efforts against climate change, Vietnam committed to greenhouse gas emission reductions by 9% by 2030 compared to the business-as-usual scenario and up to 27% with international support for the mitigation measures under the Paris Agreement.…”
Section: Introductionmentioning
confidence: 99%